Industrial engineering : concepts, methodologies, tools, and applications (Engineering Science Reference, 2013)
"This book serves as a vital compendium of research, detailing the latest research, theories, and case studies on industrial engineering"--Provided by publisher.
Keywords: Industrial engineering.; Industrial engineering -- Case studies.; elektronické knihy; electronic books